An Innovative Tai Chi and Qigong Telehealth Service in Supportive Cancer Care During the COVID-19 Pandemic and Beyond. Issue 4 (July 2021) - Oh, Byeongsang; Van Der Saag, Diana; Morgia, Morita; Carroll, Susan; Boyle, Frances; Back, Michael; Lamoury, Gillian
Supportive cancer care services, including acupuncture and Tai Chi and Qigong (TQ), are offered to cancer patients to manage cancer symptoms and/or treatment-related adverse effects and improve quality of life during and after standard care. Normal face-to-face acupuncture and TQ group services were suspended during the coronavirus (COVID-19) pandemic to reduce the risk of transmission of infection and meet social distancing restriction guidelines. This led to a sudden shift from face-to-face sessions to telehealth sessions in the health care system. We report patients' experiences of TQ telehealth services as a new initiative developed for cancer care. We found that delivery of TQ telehealth is feasible and resulted in increased overall patient satisfaction with cancer care services during the lockdown. The delivery of TQ telehealth experiences and challenges are discussed.